2017
DOI: 10.1038/s41598-017-00444-w
|View full text |Cite
|
Sign up to set email alerts
|

Real-time observational evidence of changing Asian dust morphology with the mixing of heavy anthropogenic pollution

Abstract: Natural mineral dust and heavy anthropogenic pollution and its complex interactions cause significant environmental problems in East Asia. Due to restrictions of observing technique, real-time morphological change in Asian dust particles owing to coating process of anthropogenic pollutants is still statistically unclear. Here, we first used a newly developed, single-particle polarization detector and quantitatively investigate the evolution of the polarization property of backscattering light reflected from du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 45 publications
0
55
0
Order By: Relevance
“…During the long‐range transport of Asian dust, the properties of dust should be modified due to the passing over vast populous and industrialized areas of the eastern China as well as changes of environmental conditions toward the south (e.g., higher temperature and humidity; Huang et al, ; Pan et al, ; Tobo et al, ). As shown in Figure f, two AERONET sites (i.e., Xianghe in the North China Plain and Taihu in the Yangtze River Delta) located near the dust transport pathway.…”
Section: Resultsmentioning
confidence: 99%
“…During the long‐range transport of Asian dust, the properties of dust should be modified due to the passing over vast populous and industrialized areas of the eastern China as well as changes of environmental conditions toward the south (e.g., higher temperature and humidity; Huang et al, ; Pan et al, ; Tobo et al, ). As shown in Figure f, two AERONET sites (i.e., Xianghe in the North China Plain and Taihu in the Yangtze River Delta) located near the dust transport pathway.…”
Section: Resultsmentioning
confidence: 99%
“…CC BY 4.0 License. reactions and its importance between artificial pollution and mineral dust aerosols has also been made and confirmed (Wang et al, 2017).…”
Section: Synergistic Influence Of Meteorology and Mixing Processes Onmentioning
confidence: 85%
“…backward scattering) decreased as the imaginary part of the refractive index increased (Ishimoto et al, 2010;Dubovik et al, 2006). However, Pan et al (2017) reported that variations in the refractive index of a particle can only explain limited depolarization variability (5%) on the basis of the T-matrix methodology (Dubovik et al, 2002). In other words, the observed change in the depolarization ratio in coarse mode particles in case C was mainly caused by morphological changes.…”
Section: Polarization Properties Of Polluted Dust Aerosolsmentioning
confidence: 86%
See 1 more Smart Citation
“…This assumption is validated by experimental evidences in many studies [100] and allows a full interaction between all constitutive species of particles. Nevertheless, in this version of CHIMERE the formation of coarse nitrate due to the reaction of calcium with nitric acid (issued from the anthropogenic pollution) is not considered and could enhance the interactions between natural and anthropogenic emissions as it has been studied in China [101]. The transport of "giant" mineral particles, which can be defined as particles with diameters exceeding 10 µm, is rarely documented in the literature according to a recent study [102].…”
Section: Particle Size Distributionmentioning
confidence: 99%